A survey of the conservation programs and practices on special collections and archival materials in the University of the Philippines Diliman libraries - Rebolledo, Anthony J. (Institute of Library Science, University of the Philippines Diliman, 1998)
The study is intended primarily to find out the conservation program, practices, conditions, problems and existence of the conservation of special collections and archival materials in the University of the Philippines Diliman libraries and to propose necessary measures towards the improvements. It was carried out in response to the expressed need of librarians and archivists that the development of a comprehensive library and archives requires, among others the support of an efficient and cost effective conservation program.